2001
DOI: 10.1016/s1097-2765(01)00181-2
|View full text |Cite
|
Sign up to set email alerts
|

SC35 Plays a Role in T Cell Development and Alternative Splicing of CD45

Abstract: Molecular diversity via alternative splicing is important for cellular function and development. SR proteins are strong candidate regulators of alternative splicing because they can modulate splice site selection. However, endogenous substrates for SR proteins are largely unknown, and their roles as splicing regulators in vertebrate development are unclear. Here we report that Cre-mediated conditional deletion of the prototypical SR protein SC35 in the thymus causes a defect in T cell maturation. Deletion of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 55 publications
6
117
1
1
Order By: Relevance
“…Finally, it has been shown that ablation of SC35, which also regulates alternative splicing of CD45, correlates with a reduced number of peripheral CD4 and CD8 T cells in the spleen. However, in contrast to our findings, the CD45RO isoform was predominant and CD45RB was undetectable in SC35-deficient mice (51). Although our hnRNP L 2/2 -deficient SP cells show a similar migration defect as SC35-deficient animals, higher m.w.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, it has been shown that ablation of SC35, which also regulates alternative splicing of CD45, correlates with a reduced number of peripheral CD4 and CD8 T cells in the spleen. However, in contrast to our findings, the CD45RO isoform was predominant and CD45RB was undetectable in SC35-deficient mice (51). Although our hnRNP L 2/2 -deficient SP cells show a similar migration defect as SC35-deficient animals, higher m.w.…”
Section: Discussioncontrasting
confidence: 99%
“…1 and Supplementary Table 1). These observations markedly expand the number of known endogenous alternatively spliced gene targets of SR proteins 20,[35][36][37][38] .…”
Section: Mechanism Of Sf2/asf-driven Transformationmentioning
confidence: 84%
“…S1]. Sfrs protein molecular masses are 25-28 kDa, but Sfrs proteins reportedly migrate at 35 kDa on SDS/PAGE gels (17). Proteomics analysis identified the 15-kDa protein as a fragment of annexin 1.…”
Section: Identification Of Iprsmentioning
confidence: 99%